PENGGUNAAN PRIMER GEN CYTOCHROME OXIDASE 1 DALAM REAKSI POLYMERASE CHAI REACTION (PCR) UNTUK IDENTIFIKASI KANDUNGAN BABI PADA MAKANAN - Pane, Elfira Rosa; Legasari, Leni; Mardini, Intan (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2024)
Muslims make up the majority of the population in Indonesia so halal food safety is of paramount importance. From a religious and health perspective, adulteration and contamination of Sus scrofa meat is considered a violation of halal norms. Sus scrofa is often used to adulterate beef to take advantage of the physical resemblance and price difference. The need to identify Sus scrofa meat contamination in food products was highlighted in this study. After a successful isolation process, the Polymerase Chain Reaction (PCR) method was used to validate the presence of porcine DNA. PCR utilizes primers specifically made to replicate specific DNA sequences associated with pigs. PCR testing provides precise results for pig DNA, ensuring the accuracy of detection of pork contamination in foodstuffs. This research contributes to efforts to maintain halal food safety in Indonesia by emphasizing the important role of PCR in the detection process of Sus scrofa meat.